KARAKTERISTIK PAPAN PARTIKEL KULIT BUAH KAKAO (Theobroma cacao L.) PADA VARIASI KONSENTRASI PEREKAT POLYVINYL ACETATE - Pradana, I Gusti Made Teddy; Harsojuwono, Bambang Admadi; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
The aims of this study were to know the characteristic of particle board cocoa-pod husk on variation of polyvinyl acetate (PVAc) adhesive concentration, and to have the best concentration polyvinyl acetate adhesive in particle board from cocoa-pod husk. The experiments in this study used a single factor with regression analysis. The factors are the concentration of polyvinyl acetate adhesive, that is 35%, 37.5%, 40%, 42.5%, 45% dan 47.5%. The fisis test results showed that concentration of polyvinyl acetate adhesive had upward trend on density and downward trend on moisture content, water absorption, and thickness swelling. The mechanical test result showed that concentration of polyvinyl acetate adhesive on concentration 47.5% had the best treatment. The best treatmest of particle board from cocoa-pod husk is made by used 47.5% polyvinyl acetate adhesive with density 0.48 g/cm 3 , moisture content 8,64%, water absorption 155.85%, thickness swelling 13.34% in fisis test and with MOE 44.07 kg/cm 2 , MOR 1.38 kg/cm 2 and compressive strength parallel 2.36 kg/cm 2 in mechanical test. Key words: particle board, cocoa-pod husk, polyvinyl acetate